Lipid profile in people starting antiretroviral therapy with efavirenz or dolutegravir based regimens from a reference center in Brazil: a cohort study (Research, Society and Development, 2022)
Objective:  To compare the impact on lipid profile (LP) in people starting antiretroviral therapy (ART) before e after the use with efavirenz (EFZ) or dolutegravir (DTG) based regimens. Methods: A prospective cohort study stratified into two groups, the people living with HIV (PLWHIV) who started either DTG or EFV. Dyslipidemia was defined by laboratory criteria in the period from September 2015 to October 2017. Parametric and non-parametric tests and matched pair tests were used, considering p